SÍNTESE DE PARTÍCULAS DE PLATINA EM UMA MATRIZ ORGÂNICA DE NEGRO DE FUMO PARA PRODUÇÃO DE ELETRODOS MODIFICADOS - Kalinke, Adir Hildo (2008)
In this work was developed a methodology for incorporation of platinum particles to carbon black matrices called Eeonomers (Kp0; Kp20 and Kpy20). The characterization of modified materials Kp0/Pt; Kp20/Pt and Kpy20/Pt was performed by SEM / EDX; XRD; TEM and Cyclic Voltammetry (VC). Measures of the SEM coupled to EDX showed that the platinum particles were homogeneous distributed in the carbon matrix. Meanwhile, the average size of nanoparticles were estimated between 3 and 7 nm through calculations with the application of the Scherrer’s equation and were confirmed by MET measurements. The VC confirmed the incorporation of particles by the increase of faradaics current in negative and positive extremes of the potencial scan range assigned to the generation of oxygen and hydrogen due to the presence of platinum incorporated to the modified materials. These modified materials were used in the production of electrodes and were applied in electroanalysis used for determination of dopamine and for oxidation of methanol. The electrodes modified with platinum (EPC/Kp0/Pt, EPC/Kp20/Pt e EPC/Kpy20/Pt) showed no effects of electrooxidation for dopamine, as was expected and therefore, did not justify a modification of the material due to the high cost of platinum. Nevertheless, the electrodes of Kp0/Pt and Kp20/Pt were efficient in electrooxidation of methanol in all concentrations and can be used to replace the smooth platinum, since it increased the number of available active sites even in smaller concentrations investigated. This surface area of available platinum in the modified electrodes was calculated by the difference of integrals of the first and second cycles during the process of cyclical scanning in measures of CO adsorbed considering a load of platinum smooth at 484 μ C.cm2. Key words: Carbon black, Eeonomers, carbon paste electrodes, Cyclic Voltammetry